THE IMPORTANCE OF FOREIGN DIRECT INVESTMENT IN THE ECONOMIC DEVELOPMENT - Rustam Islamovich Ramazonov (Journal Park Publishing, 2022)
The article provides a theoretical study of the importance of investment in the country's economy, the expected level of return on investment and investment strategy, and develops practical proposals and recommendations in this regard.
Keywords: investment, policy, technology